Biochemical indices of response to hydroxychloroquine and sodium aurothiomalate in rheumatoid arthritis. Issue 5 (October 1981) - Dixon, J S; Pickup, M E; Bird, H A; Lee, M R; Wright, V; Downie, W W
Abstract : Biochemical and clinical changes have been monitored in 30 patients with rheumatoid arthritis treated with either hydroxychloroquine or sodium aurothiomalate over a period of 6 months. Acute-phase reactants improved in both treatment groups, while serum sulphydryl and serum histidine improved only in the gold-treated patients. Correlation matrices were constructed from mean clinical and biochemical data at successive clinic visits. Correlations obtained with gold were more frequent and of a higher level of significance than those obtained with hydroxychloroquine at the doses we studied. This lends support to the use of correlation matrices as a screening test for potential long-term antirheumatoid activity of drugs in man.